Social structure and organizations revisited - Lounsbury, Michael; Ventresca, Marc J. (Research in the sociology of organizations ;, 2002)
This work brings together empirical research and thematic commentaries which chart out research directions for politically-inflected studies of organizational and institutional change. The chapters give practical voice to the theoretical questions and research designs of an emerging agenda for organization theory that engages questions about broader social structure and organizations with theory in cultural analysis, stratification, and entrepreneurship. Cases include historical studies of the evolution of the fire insurance industry in the 19th century, studies of the organizational vitality of contemporary evangelical Protestantism, the emergence of gay and lesbian identity organizations, challenges in the institutional structuring of the mutual fund industry the post-Soviet Russia, stratification and status organizing processes in entrepreneurial organizations, studies of social movements and organizations, both external to and inside of organizations.